A Systematic Literature Review: Augmented Reality-based Learning Media to Improve Student Learning Outcomes - Ratnasari, Yanuar Meta; Fakhruddin, Fakhruddin; Ahmadi, Farid; Subali, Bambang; Widiarti, Nuni (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to analyze the results of previous research on the effect of augmented reality-based learning media on student learning outcomes in science learning at the elementary school level. The rapid development of technology invites us to continue to adapt so as not to be far behind. Augmented Reality presents abstract concepts in layers so students can witness them in real-time through time through augmented reality-based interactive comic media; students are invited to directly observe abstract ideas in their hands, thus creating more meaningful learning. Using the Systematic Literature review method, researchers analyzed 25 articles from 15 international journals and 10 national journals from 2019 to 2025 to determine the effectiveness of augmented reality-based learning media in improving student learning outcomes in science learning. The articles were obtained based on search results from publish or perish. The results of previous studies show that augmented reality-based learning media can consistently improve student learning outcomes in science learning. This study concludes that using augmented reality-based learning media has significant potential in supporting science learning and presenting fundamental concepts behind abstract concepts complex for students to understand. This discovery will likely encourage using augmented reality-based media in education more widely and effectively.